145 Impact of the exercise training programme offered to type 2 diabetes patients within the DIALOGS network. (23rd September 2015) - Martin, C; Odin, F; Larmaraud, M P
Abstract : Background and Objectives: The objective of the DIALOGS network in South-East France (counties: Rhône, Ain and part of Isère) is to help improve the management of patients with type 2 diabetes by offering therapeutic patient education sessions, free consultations on diet, a yearly visit to a podiatrist (patients with grades 0 and 1), two dental check-ups including dental scaling per year, and free support for smoking cessation. Programme: Patients who are members of the network can also benefit from support from a physical activity trainer to help them resume physical activity. This may take place either in a club or as part of the activities offered by the network: walking, Nordic walking, water aerobics, gymnastics and fitness. Among the 633 network members, 237 chose physical activity as a means of improving their metabolic status. Of these, 118 were willing to undergo a physical activity check-up and follow-up by the physical activity trainer; 70 chose a physical activity offered by the network. Results: At the beginning of the study, patients who chose to improve their physical activity (PA) were on average already more active: 34% were sedentary vs 58.2% amongst those who chose other actions. They were older (60.8 vs 59.5 years) and had a higher body mass index (BMI) (32.4 vs 31.1). However, there was no difference in anxiety/depression scores (9/6 in both sets of patients), blood pressure (133/77 for PA vs 134/77), triglycerides (1.57 for PA vs 1.7 g/l), HDL cholesterol (0.53 vs 0.54 g/l), LDL cholesterol (1.17 vs 1.07 g/l) or condition of the feet. Glycated haemoglobin (HbA1c) levels were 7.45% vs 7.7% initially, and 6.9% vs 7.4% after 2 years of monitoring within the network. There was no difference in weight at two years (BMI 30.5 for PA vs 30.2). Physical activity was moderate in 50% of patients who chose PA and moderate-to-sustained in the other 50%. Overall, 49% of the patients who chose other actions were still sedentary. Conclusion: Even patients who express a desire to undertake a physical activity find implementation difficult. Weight and age are not limiting factors. The practice of a physical activity of moderate-to-sustained intensity had a beneficial effect on glycaemia but did not affect weight any more than did other types of action undertaken by patients. Contexte et objectifs: Le réseau DIALOGS prend en charge les diabétiques de type 2. Il couvre les départements du Rhône, de l'Ain et d'une partie de l'Isère. Son objectif est d'aider à une meilleure prise en charge des diabétiques de type 2 en proposant aux patients différents avantages. Outre les séances d'éducation thérapeutique, sont proposées aux adhérents des consultations diététiques gratuites, une consultation par an de soins de podologie pour les grades 0 et 1, 2 bilans bucco-dentaires et détartrage dans la même consultation par an et la prise en charge gratuite du sevrage tabagique. Programme: Les patients qui le souhaitent bénéficient également de l'aide d'un éducateur médico-sportif (EMS) pour leur reprise d'activité physique, soit dans un club, soit parmi les activités proposées par le réseau: marche, marche nordique, aquagym, gymnastique et remise en forme. Parmi les 633 patients adhérents du réseau, 237 ont choisi comme objectif pour améliorer l'équilibre de leur diabète: l'activité physique. Seulement 118 ont finalement accepté un bilan d'activité physique avec suivi par l'EMS, dont 70 ont une activité dans le cadre du réseau. Résultats: Les patients qui ont choisi d'améliorer leur activité physique avaient déjà en moyenne une activité physique plus importante: activité sédentaire: 34% contre 58.2% pour ceux qui ont choisi un autre objectif. Par rapport aux patients du réseau ayant choisi un autre objectif (AO), les patients ayant choisi d'améliorer leur activité physique (AP) sont plus âgés: 60.8/59.5 ans, plus gros: IMC 32.4/31.1 L'on ne retient pas dans les 2 groupes de différence de score anxiété/dépression (9/6 dans les 2 cas), de la tension artérielle AP/AO: 133/77 – 134/7, 7des triglycérides: 1.57/1.7 g/l, HDL cholestérol: 0.53/0.54 g/l du LDL cholestérol: 1.17/1.07 g/l ou de l'état des pieds. Les taux d'HbA1c sont respectivement de 7.45 et 7.7% et évoluent à 2 ans de prise en charge à 6.9 et 7.4%. Après 2 ans de suivi on ne note pas de différence de poids dans les 2 groupes: IMC 30.5/30.2 mais l'activité physique est modérée pour 50% et modérée soutenue pour 50% des AP et sédentaire pour encore 49% des AO Conclusion: La mise en pratique d'une activité physique même chez les patients qui en annoncent le désir est difficile à mettre en œuvre. Le poids et l'âge ne sont pas des facteurs limitants. La pratique de l'activité physique avec une intensité modérée à soutenue a un effet bénéfique sur l'équilibre du diabète mais ne modifie pas plus le poids que d'autres actions qui ont pu être proposées aux autres patients.